Effect of Low Lactose Milk Eiwit Melk (E.M.) on Protein Calorie Malnutrition - Suharjono Suharjono; I.G.N. Wila Wirya; Samsudin Samsudin; Sunoto Sunoto; Z. Sulaiman; Sutedjo Sutedjo (Indonesian Pediatric Society, 1975)
During 1Â½ years, from January 1972 until July 1973, 55 P.C.M. children hospitalised in the Department of Child Health, Medical School, University of Indonesia/Dr. Tjipto Mangunkusumo General Hospital, were involved to this study. Self-prepared